(untitled) (International journal of artificial intelligence, 2025)
This paper discusses the comparative error-correcting ability of block codes such as Hamming, Golay, BCH, and Reed-Solomon codes. The introduction emphasizes the importance of ensuring reliable data transmission under real-world interference conditions such as thermal noise, multipath propagation, and impulse interference. Methods for improving noise immunity are discussed, including convolutional and block coding. The paper presents analytical formulas for calculating the probability of errors in decoded messages using various codes. The calculation results confirm that the error-correcting ability depends on the code parameters and the error probability in the channel. A study is conducted on the efficiency of codes in the presence of burst errors of different lengths, including conditions under which decoding remains successful. The paper emphasizes that the choice of the optimal code is determined by the specifics of the telecommunication system and the characteristics of the communication channel.